Harmonization of Partnership Regulations in the Plantation Business Sector to Achieve Legal Certainty (Case Study of The CSR Sugarcane Partnership Program of PT Sukses Mantap Sejahtera with Farmers) - Yuliana, Yuliana; Gultom, Elisatris (Riviera Publishing, 2026)
The plantation business sector has an important role in the national economy, especially through partnership programs as part of Corporate Social Responsibility (CSR). However, partnership arrangements in this sector are still characterized by complexity and disharmony of laws and regulations that cause obstacles in its implementation and legal uncertainty for business actors. This study aims to understand the regulation of partnership programs in the plantation sector in accordance with national regulations as well as to examine the harmonization of regulations in order to create legal certainty. The methods used are normative juridical and empirical juridical approaches with data collection techniques in the form of library research and field studies at PT Sukses Mantap Sejahtera. Data analysis was conducted normatively descriptively. The results showed that regulations related to partnerships issued by the Ministry of Agriculture, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, and CSR regulations in the plantation sector are often not harmonized, thus separating CSR obligations and facilitation of community plantation development even though both have the same goal, namely improving the welfare of farmers and business sustainability. This disharmony creates multiple administrative and investment burdens, hampering the optimization of partnership programs and creating legal uncertainty. The research recommends the need for harmonization and revision of partnership regulations in the plantation sector to be integrated and non-overlapping, thus supporting a conducive investment climate and sustainable development. The implementation of this harmonization is expected to facilitate the implementation of partnership CSR programs, including in the case of PT Sukses Mantap Sejahtera, and support the achievement of national sugar self-sufficiency.